Food Selectivity, Mealtime behavior, Weight status and Dietary intake in Children and adolescent with Autism - Upadhyay-Dhungel, Kshitiz; Ghimire, Sukriti (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Food selectivity is a common parental concern in childhood that can become problematic and lead to issues such as nutritional deficits that may impair growth and development. Considering the problem of food selectivity and meal time behaviors in the children with autism, this study was undertaken to assess their food selectivity, mealtime behavior problems, nutrient intake and weight status of children and adolescent with autism of Autism Care Nepal Society. Material and methods: This is a descriptive cross sectional study carried out in Autism children and adolescent aged 3-19 years in Autism Care Nepal Society. The sampling method was purposive sampling by total enumeration method. A pretested structured questionnaire was used to collect data using a face-to-face interview. Data were entered and analyzed in Microsoft Excel. Descriptive analysis was done to determine the socio-demographic characteristics. Chi-square test was done to determine the association of different independent variables with the BMI. Results: Out of 70 participants, 49 were male and 29 females. Among 70 participants, about 4% individuals were underweight, 39% normal and 57% were overweight or obese (≥85th percentile). Out of this 36% were obese (≥95th percentile). Out of 70 participants, 36 individuals (51.43%) were food selective while 34 individuals (48.57%) were not food selective that 51.43% of autism children and teenagers do not have problematic meal time behavior while 48.57% of them have problematic meal time behavior. Conclusion: There was no significant association between age, gender, family income, physical activity, food selectivity and mealtime behavior with BMI (p>0.05) among autistic children. However, food selectivity of the autistic participants showed a significant association with obesity. There was significant difference in mean calorie intake by all the age groups than the calorie set intake by Indian council of Medical Research (ICMR) as p-value was <0.05 in all age group.